United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes the impact of globalization inflation and relative prices over the last decade in the United Kingdom. The IMF's Global Economy Model is used to estimate the relative importance of the various factors argued to have influenced the evolution of inflation and relative prices over this period. The key result is the significantly different impact of the shock on relative prices in the United Kingdom compared with the United States and the Euro area. The paper also explores the likely evolution of the economy after a rise in immigration.